2021
DOI: 10.1038/s41598-021-96089-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lenvatinib for unresectable hepatocellular carcinoma based on background liver disease etiology: multi-center retrospective study

Abstract: It was recently reported that hepatocellular carcinoma (HCC) patients with non-alcoholic steatohepatitis (NASH) are not responsive to immune-checkpoint inhibitor (ICI) treatment. The present study aimed to evaluate the therapeutic efficacy of lenvatinib in patients with non-alcoholic fatty liver disease (NAFLD)/NASH-related unresectable-HCC (u-HCC). Five hundred thirty u-HCC patients with Child–Pugh A were enrolled, and divided into the NAFLD/NASH (n = 103) and Viral/Alcohol (n = 427) groups. Clinical features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Currently, the only proposed strategies for HCC are loco-regional treatments (i.e., hepatic resection, ablation, transarterial chemoembolisation), inhibitors of tyrosin kinase/anti-angiogenetic agents, as Sorafenib, Regorafenib and ramucirumab, and ultimately liver transplantation [ 50 ]. Very recently also Lenvatinib, an oral multikinase inhibitor, was confirmed as non-inferior to Sorafenib in untreated advanced hepatocellular carcinoma [ 51 , 52 ].…”
Section: Immune-related Therapy In Nafldmentioning
confidence: 99%
“…Currently, the only proposed strategies for HCC are loco-regional treatments (i.e., hepatic resection, ablation, transarterial chemoembolisation), inhibitors of tyrosin kinase/anti-angiogenetic agents, as Sorafenib, Regorafenib and ramucirumab, and ultimately liver transplantation [ 50 ]. Very recently also Lenvatinib, an oral multikinase inhibitor, was confirmed as non-inferior to Sorafenib in untreated advanced hepatocellular carcinoma [ 51 , 52 ].…”
Section: Immune-related Therapy In Nafldmentioning
confidence: 99%
“…In contrast to ICI, previous studies have reported that lenvatinib is equally effective in NASH-HCC with other etiologies [87] and more effective against NASH/NAFLDassociated HCC than against HCC with alcohol or viral etiologies [88]. Therefore, when a patient is clinically suspected to present NASH-HCC and does not respond to atezolizumab plus bevacizumab therapy, the treatment should be immediately switched to lenvatinib or another therapy associated with improved disease status.…”
Section: The Efficacy Of Atezolizumab Plus Bevacizumab Combination Therapy Against Nash-hccmentioning
confidence: 99%
“…The efficacy of lenvatinib does not appear to be influenced by the etiology of the liver disease. Hiraoka et al recently conducted a multicentre retrospective study with 103 patients with NAFLD and 427 patients with AFLD or viral -related HCC treated by lenvatinib [ 58 ] without significant difference in overall survival (OS) (20.5 vs. 16.9 months, p = 0.057) between viral and NAFLD group.…”
Section: Could Lenvatinib Compete With Atezolizumab Plus Bevacizumab?mentioning
confidence: 99%